Settlement-Time Aspect for Equal-Area Footings with Polygon Shapes Lying on Gypseous Soil - Saleem M. Imariq; Waad A. Zakaria; Hassan O. Abbas (Tikrit Journal of Engineering Sciences)
Gypseous soil is one type of collapsible soil. It is well known in Iraq for causing structural distress to many engineering facilities. It is characterized as having high strength properties as being dry, but when wetted with water, it experiences rapid collapse settlement. The present laboratory study evaluates the collapse settlement for several polygons and non-common footing shapes and compares them. In some structural facilities, such problems may arise when using polygon footing shapes due to reasons regarding non-uniform spacing left for footing, restrictions due to property lines or sanitary works. For this purpose, a large laboratory tank model had lateral dimensions of 0.8× 1.0m and a depth of 0.8m. The studied gypseous soil, with 63% gypsum content, was from Tikrit City, about 200km north of Baghdad/ Iraq. It is compacted to a dry unit weight of 14.82kN/m3 in the model. The used shapes of footings were a square, circular, equilateral triangle, rectangular, plane strain, trapezoidal, and isosceles triangle. All footings were (100 cm2) and bear the same applied pressure (40kN/m2). Both dry and then soaking stages for soil were conducted. The experiments were conducted, such as one test for each tank. The test results revealed that the maximum collapse settlement recorded was in the case of the isosceles triangle, i.e., (settlement/equivalent width) ratio Δs/B is 0.24. The least collapse settlement was for the case of square footing with a Δs/B of 0.15. The settlement measured when the soil dried was about 1-1.3 mm for all footing shapes, i.e., Δs/B=0.01-0.013. The collapse settlement stopped after 5-7 days, while the dry condition settlement took less than one hour to level off and end.